Software for Pre-design of landfill by method intended from the trenches of smaller municipalities - Santos, Layara de Paula Sousa; Mendes, Thiago Augusto; Abreu, Gustavo Rodrigues de Oliveira; Santos Neto, Agenor Sousa; Leitão, Valéria de Sousa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
The work was mainly intended to subsidize design elements and management to develop computer application involving the preliminary design of landfills by the method of the trenches for the small municipalities. The computational tool (software) developed in Java requires input data to be supplied by the user so that it processes the calculations for disposal of urban waste and health in landfills run by the method of the trenches. After the entry of data by the user, click on the button "CALCULATE" of the software, then calculations, tables and graphics output is processed and can now be viewed and analyzed. The results of preliminary design for different scenarios (input data) obtained were satisfactory as presented validity compared with the calculation script established by the different academic references of the area as Kroetz (2003) and Ferreira (2008).